1994
DOI: 10.1046/j.1471-4159.1994.63010256.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic Demonstration of Increased α2‐Adrenoceptor Agonist Binding Sites in the Hippocampus and Frontal Cortex of Depressed Suicide Victims

Abstract: To examine directly in the brain the status of α2‐adrenoceptors in major depression, the specific binding of the agonist [3H]UK 14304 was measured by quantitative receptor autoradiography in the hippocampus and frontal cortex of suicide victims (n = 17) with a retrospective diagnosis of depression (n = 7) or other psychiatric disorders (n = 10) as well as of matched control subjects (n = 9). In suicide victims, a significant increase in the number of α2‐adrenoceptors was found in the CA1 field (40%) and dentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 44 publications
2
47
0
1
Order By: Relevance
“…Suicide victims have increased numbers of alpha-2A adrenergic receptors and mRNA expression in the hippocampus and frontal cortex (Escriba et al, 2004;Garcia-Sevilla et al, 1999;Gonzalez et al, 1994). Moreover, the ADRA2A receptor gene is located on chromosome 10q24-q26, a region that has been linked to SB in genome-wide linkage studies (Cheng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Suicide victims have increased numbers of alpha-2A adrenergic receptors and mRNA expression in the hippocampus and frontal cortex (Escriba et al, 2004;Garcia-Sevilla et al, 1999;Gonzalez et al, 1994). Moreover, the ADRA2A receptor gene is located on chromosome 10q24-q26, a region that has been linked to SB in genome-wide linkage studies (Cheng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, using specific antibodies, have demonstrated that the density of a 2A -adrenoceptor is increased in suicide subjects with major depression . In addition, other studies using radioligand agonists revealed an elevation in the density of a 2A -adrenoceptor (high-affinity state) in the post-mortem brains of suicide victims (Callado et al, 1998;De Paermentier et al, 1997;González et al, 1994;Meana et al, 1992;Meana and García-Sevilla, 1987). In addition, higher levels of G i proteins (García-Sevilla et al, 1996b, 1999 and lower levels of adenylyl cyclase activity (Reiach et al, 1999) were reported in the platelets of depressed subjects and post-mortem brains of suicide victims who previously suffered from depression.…”
Section: Alterations In a 2a -Ar Expression In The Brains Of Suicidesmentioning
confidence: 97%
“…serve as auto-or heteroreceptors, and control neurotransmitter release (Schlicker and Göthert, 1998;Starke, 1981). There is evidence that the density of some of these GPCR proteins, such as a 2 -adrenoceptors and 5-HT receptors, is altered in the brains of suicide victims and in the platelets of depressed patients (Callado et al, 1998;De Paermentier et al, 1997;García-Sevilla et al, 1986, 1999González et al, 1994;Meana et al, 1992;Meana and García-Sevilla, 1987;Mendelson, 2000;Ordway et al, 1994;Pandey et al, 1995;Sargent et al, 2000;Stockmeier et al, 1998). These alterations have been correlated with impaired neurotransmitter release that results from a 2 -adrenoceptor supersensitivity and/or serotonin receptor dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12]14 A lack of differences in the agonist radioligand binding density of ␣ 2 -adrenoceptors has also been reported between subjects with major depression and controls. 45,46 The more rigorous diagnosis methodology (psychological autopsy vs searching of established medical records in the present study), the stricter inclusion and exclusion criteria, and the careful matching one-to-one reported herein could explain the apparent discrepancies between authors.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…Among them, ␣ 2 -adrenoceptors, -opioid, GABA B and cholinergic muscarinic M 2 /M 4 receptors, by acting as autoreceptors or heteroreceptors, contribute to the inhibition of neurotransmitter release. [5][6][7] In depressed suicide victims, high densities of brain ␣ 2 -adrenoceptors have been found in terminal areas of NE and 5-HT pathways [8][9][10][11][12][13] and at the somatodendritic level of noradrenergic cells. 14 Many antidepressant treatments are able to modulate ␣ 2 -adrenoceptor density and/or function.…”
Section: Introductionmentioning
confidence: 99%